PENERAPAN HUKUM DE MOIVRE PADA PENENTUAN NILAI CADANGAN PREMI ASURANSI JIWA JOINT LIFE - NOVALINDA, RIZKA AULIA; WIDANA, I NYOMAN; JAYANEGARA, KETUT (E-Jurnal Matematika; Vol 11 No 1 (2022), 2022)
Joint life insurance is  a single policy that  covers two lives. The benefit is paid out when the first person dies.  Insurance companies need to calculate and assign premiums and a policy value  in order to know. the expected  value of the future loss.  The study used the quantitative data of mortality for men and women obtained from the Indonesian Mortality Table (TMI) 2011. Data analysis techniques use the New Jersey method of prospects and a legal approach of mortality that is De Moivre’s law. The  purpose  of this study  is to determine  policy value on joint life insurance that applies to De Moivre's laws and compare policy value on joint life insurance that applies De Moivre's laws and without the application of De Moivre's laws. Research shows that joint life insurance policy value with New Jersey methods of prospective and application of De Moivre's law always come into value smaller than those without an application of De Moivre's law, but at the end of period both are worth the same according to the value of their benefits.